Respuesta :
The graph passes through the points (2,2) and (6,6)
This means
f(2) = 2
f(6) = 6
The average rate of change of f(x) x = 2 to x = 6 will be:
[tex] \frac{f(6)-f(2)}{6-2} = \frac{6-2}{4}= \frac{4}{4}=1 [/tex]
Thus the average rate of change of given function from x = 2 to x = 6 is 1
This means
f(2) = 2
f(6) = 6
The average rate of change of f(x) x = 2 to x = 6 will be:
[tex] \frac{f(6)-f(2)}{6-2} = \frac{6-2}{4}= \frac{4}{4}=1 [/tex]
Thus the average rate of change of given function from x = 2 to x = 6 is 1
Answer:
The average ate of change for f(x) from x=2 to x=6 is one, (1). Also seen as choice c.
Step-by-step explanation: